Depression Among Elderly living in Nursing Homes - Sanga, Jumiati Lelu; Adawiyah, Asyifa Robiatul; Djokosujono, Kusharisupeni; Sudirman, Herman (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: Depression that occurs in older people can interfere the psychomotor activities such as slowing body movements and verbal responses. The elderly who have depression will ignore themselves and their appearance and lose interest in interacting with other people which has an impact on decreasing their quality of life. Methods: This is a descriptive-analytic study using a cross-sectional approach to find depression among older people living in nursing homes. The sample size was measured by the Lemeshow formula 95% confidence interval with purposive technical sampling. A total of 103 elderly (those aged ≥60 years) lived in Padu Wau nursing home and Budi Agung nursing home, Kupang East Nusa Tenggara. Questionnaires were distributed to study participants consisting of sociodemographic characteristics, geriatric depression scale, sleep quality, and generalized anxiety disorder. Statistical analysis used descriptive and logistic regression analysis. Results: the average age of study participants is 74.51 years old (SD ± 7.73; min-max=61-90 years old). Multivariable logistic regression model showed that female (OR = 6.75; 95% CI = 1.89 to 24.12), sleep quality (OR = 12.08; 95% CI = 1.46 to 99.65), and anxiety (OR = 3.52; 95% CI = 1.04 to 11.94) is significantly associated with depression among older people who lived in nursing homes. Conclusions: female elderly, poor sleep quality, and anxiety contribute to the risk of depression in older adults. KEYWORDS: elderly; sleep quality; depression; nursing home